Cow dung extract as a low-cost and natural sensitizer for zinc oxide nanoparticles photoanode based dye-sensitized solar cell: A novel initiative for waste to energy conversion - Suresh S.; Prabu K.M.; Arivuselvi R.; Kandasamy M.; Pugazhenthiran N.; Karthick Kumar S.; Jothilakshmi R.; Murugesan K. (Elsevier B.V., 2024)
Cow dung extracts are prepared using ethanol and methanol as solvents. Electronic absorption spectra of cow dung extracts have exhibited wide absorption in the UV and visible region between 300 and 730 nm. The absorption of cow dung extracts showed variations in intensity and absorption peaks at different wavelengths, which can be attributed to presence of diverse photosynthetic pigments corresponding to polarity of applied solvents. The observed pigments of chlorophyll a, chlorophyll b and carotenoids in the cow dung extracts can be ascribed to the feeding behavior of the cow. The FTIR and UVvis absorption results have disclosed that the sensitization of zinc oxide nanoparticles (ZnO NPs) photoanode is mainly due to the chlorophylls present in the cow dung extract. The methyl group in the chlorophyll molecules from ideal bond with ZnO NPs that enables transfer of electrons from chlorophyll molecules to conduction band of ZnO NPs. The solar cells sensitized with cow dung extract in methanol has delivered highest energy conversion efficiency of 0.102%, which can be ascribed to presence of relatively a greater number of photosynthetic pigments. 2023 The Author(s)